ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS GAYAMAN KABUPATEN MOJOKERTO - Saktio Pratama, Aldiansyah; Nurwidji; Arief Fardiansyah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Patient satisfaction is very important and is the most frequently discussed issue. Patient satisfaction at the health centre itself depends on the subjectivity of the patient. The purpose of this study was to analyse the effect of service quality on patient satisfaction at Gayaman Health Centre, Mojokerto Regency. This research includes quantitative research where this research includes survey research conducted in May - August 2023. The population in this study were all patients/families of patients at Gayaman Health Centre, Mojokerto Regency who were registered at inpatient and outpatient counters. The sample used was accidental sampling, the sampling technique used was Accidental Sampling. The validity test tests whether the question is valid or not can be done through the Excel Statistical Analysis computer program, while the reliability test has a Cronbach's Alpha value above 0.60. The simple regression test result a = 3.266 is a constant value, which means that if X is considered 0, the patient satisfaction value is 3.266, b = 0.425 which is positive. Based on the description and analysis, it is known that service quality has a positive effect on patient satisfaction. Judging from the validity test of service quality on consumer satisfaction (patients) meets the requirements because the correlation value has a value above 0.2732. most patients / families of patients agree (satisfied) in terms of physical appearance (tangibles) with a percentage of 48%, reliability (reliability) 48%, and assurance and empathy (empathy) 44%.